DEVELOPMENT OF TECHNOLOGY OF PRODUCTION OF COLD-SHAPED REINFORCING STEEL ACCORDING TO THE AUSTRIAN STANDARD ONORM В 4200 - S. N. Kolos; A. V. Zinovenko; L. A. Loktionova (Литьë и металлургия)
It is shown that the developed technology of melting, pouring, rolling allowed to receive cold-shaped reinforcing steel, corresponding to the requirements of Austrian standard ONORM В 4200.